In vitro anthelmintic activity and phytochemical characterization of Colchicum autumnale L. corm extract - Zeenath Banu; Shara sherlin Jagannadham; Jangala Akanksha Akanksha; Aakula Nikshitha Aakula Nikshitha (Shiraz University of Medical Sciences, 2024)
Helminth infections are prevalent in poverty-stricken areas and developing countries with warm, humid climates and poor sanitary conditions. The limited availability of anthelmintic drugs and the emergence of drug resistance have prompted the search for new treatment options. Medicinal plants, traditionally used for treating various ailments, including parasitic infections, have been explored as sources of novel anthelmintic compounds. To evaluate the preliminary phytochemical analysis and in vitro anthelmintic activity of Colchicum autumnale L. corm extract. The anthelmintic activity of C. autumnale corm extract was tested against Pheretima posthuma (earthworms). Five different concentrations (20, 40, 60, 80, and 100 mg/ml) of the C. autumnale extract were used, alongside the standard drug albendazole at the same concentrations. The time taken for paralysis and death of the worms was recorded. The preliminary phytochemical qualitative analysis of the ethanolic extract showed the presence of alkaloids, carbohydrates, glycosides, saponins, phenols, tannins, and steroids. The study highlighted the potential of C. autumnale extract as a natural anthelmintic agent. The dose-dependent activity suggested that higher concentrations of the extract provided more effective anthelmintic action. However, further research is necessary to establish the optimal dosing, safety, and in vivo efficacy of the extract.